The Effect of Fiscal Policy on Economic Growth in Asean-5 Countries - Ainul Latifah, Mohd Yunus (2011)
This thesis study the panel data to investigate the problem of fiscal deficit at five ASEAN countries namely Indonesia, Malaysia, Philippines, Thailand and Vietnam. Beside that, this analysis used the fiscal variable and country characteristics as the variable in this model based on GDP per capita. The variables in fiscal variable consist of total tax revenue (TTR), non tax (NT), productive expenditure (PE), total expenditure (TE), and budget deficit (BD). While for country characteristics the variable are population growth (PG), investment (I), government debt (GD) and external debt (ED). This thesis examines the standard method test for panel unit root test there is Maddala and Wu (1999). After that this thesis applies the cointegration method based on panel cointegration test by Pedroni (1999). A fully modified OLS (FMOLS) test is used to estimate the long run relationship in fiscal deficit at ASEAN-5 countries. As a result, we find out that all the variables are significant between them. This thesis recommends that policymakers should concern all of the significant variables since they give impact on fiscal deficit.